Rac1 GTPase Promotes Interaction of Hematopoietic Stem/Progenitor Cell with Niche and Participates in Leukemia Initiation and Maintenance in Mouse. (27th March 2016) - Chen, Shuying; Li, Huan; Li, Shouyun; Yu, Jing; Wang, Min; Xing, Haiyan; Tang, Kejing; Tian, Zheng; Rao, Qing; Wang, Jianxiang
Abstract: Interaction between hematopoietic stem/progenitor cells (HSPCs) with their niche is critical for HSPC function. The interaction also plays an important role in the multistep process of leukemogenesis. Rac1 GTPase has been found to be highly expressed and activated in leukemia patients. Here, by forced expression of constitutively active form of Rac1 (Rac1-V12) in HSPCs, we demonstrate that active Rac1 promotes interaction of HSPC with niche. We then established an active Rac1 associated acute myeloid leukemia (AML) model by expression of Rac1-V12 cooperated with AML1-ETO9a (AE9a) in mouse HSPCs. Compared with AE9a alone, Rac1-V12 cooperated with AE9a (AER) drives an AML with a short latency, demonstrating that activation of Rac1 GTPase in mice promotes AML development. The mechanism of this AML promotion is by a better homing and lodging of leukemia cells in niche, which further enhancing their colony formation, quiescence and preventing leukemia cells from apoptosis. Further study showed that an inhibitor targeting activated Rac1 can increase the efficacy of chemotherapeutic agents to leukemia cells. This study provides evidence that activation of Rac1 promotes leukemia development through enhancing leukemia cells' homing and retention in niche, and suggests that inhibition of Rac1 GTPase could be an effective way of eliminating AML cells. Abstract : By establishing an active Rac1 associated acute myeloid leukemia (AML) model via expression of Rac1-V12 cooperated with AML1-ETO9a (AE9a) in mouse hematopoietic stem/progenitor cells, we show that compared with AE9a alone, Rac1-V12 cooperated with AE9a (AER) drives an AML with a short latency, demonstrating that activation of Rac1 GTPase in mice promotes AML development. The mechanism of this AML promotion is by a better homing and lodging of leukemia cells in niche, which further enhancing their colony formation, quiescence and preventing leukemia cells from apoptosis. Further study shows that an inhibitor targeting activated Rac1 can increase the efficacy of chemotherapeutic agents to leukemia cells.